Relationship between depression improvement and activities of daily living recovery in patients with fractures - Shunji Araki; Takahiro Ogawa; Yoshikazu Takaesu (PCN Reports)
Abstract Aim This study aimed to investigate the relationship between improvement in depressive symptoms and activities of daily living (ADL) recovery in older patients with fractures in convalescent rehabilitation wards. Methods A retrospective observational study was conducted with 144 older patients with fractures and depressive symptoms (Geriatric Depression Scale score ≥ 5) on admission, who underwent rehabilitation at a Japanese hospital from 2018 to 2023. ADL recovery was assessed by the Functional Independence Measure (FIM). Patients were classified into three groups based on change in depressive symptoms: remission, partial improvement, and no improvement. Multivariate linear regression analysis was used to evaluate factors associated with change in the FIM score. Results Remission (β = 0.184, p = 0.019) and partial improvement in depressive symptoms (β = 0.204, p = 0.009) were positively associated with change in the FIM score. Conversely, antidepressant use (β = −0.250, p = 0.002) was negatively associated with change in the FIM score. Conclusion Remission and partial improvement in depressive symptoms positively contributes to ADL recovery in older patients with fractures. Comprehensive interventions addressing both depression and physical function may enhance rehabilitation outcomes. This may improve ADL recovery and long‐term prognosis in older patients with fractures.